PROBLEMATYKA ODPOWIEDZIALNOŚCI ORGANU ODSZKODOWAWCZEGO - Orlicki, Marcin (Zeszyty Prawnicze, 2017)
Civil Responsibility Of Compensation Body Summary A compensation body plays a key role in a system created by The Fourth Motor Insurance Directive (Directive 2000/26/EC) in order to protect victims of road accidents abroad. Its aim is to discipline insurance undertakings - namely the compensation body is competent to satisfy claims raised by injured parties on behalf of, and on account o f the insurer who does not fulfil his obligations. Answering a question whether the compensation body should have a guarantee function (i.e. when an injured party has a claim against it), or a merely relief function (i.e. satisfaction o f a claim is w ithin its own discretion), is here of crucial importance. T hat could be easily noticed that as for the compensation body’s functions, there is a discrepancy between the European and the Polish legislator (the views of the latter are expressed in the provisions of The Compulsory Insurance, Insurance Guarantee Fund and Polish MotorInsurers’ Bureau Act, implementing the above m entioned Directive) andthis article aims at analysing that problem. Firstly, it describes a model ofthe compensation body included in the provisions of The Fourth MotorInsurance Directive. Secondly, it focuses on the content of respectiveprovisions of The Compulsory Insurance Act, expressing ideas of thePolish legislator.